2022
DOI: 10.1038/s41443-022-00645-6
|View full text |Cite
|
Sign up to set email alerts
|

The broad reach and inaccuracy of men’s health information on social media: analysis of TikTok and Instagram

Abstract: Social media (SoMe) offers great potential to expand access to health information, but a significant proportion of users consume its content instead of consulting a physician. We sought to quantify the volume and characterize the accuracy of men’s health-related content on TikTok and Instagram. We searched TikTok and Instagram for the terms: testosterone, erectile dysfunction, male infertility, semen retention, Peyronie’s disease, and vasectomy. The top 10 hashtags for each term were used to estimate the total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The high quality of information and the lack of misinformation on ED from AI chatbots contrast with previous studies showing the prevalence of misinformation about ED on social media platforms [1,2]. This is reassuring as AI chatbots continue to rise in popularity.…”
Section: Top Five Google Trend Queries Total (Googe Trends + Niddk He...mentioning
confidence: 76%
See 2 more Smart Citations
“…The high quality of information and the lack of misinformation on ED from AI chatbots contrast with previous studies showing the prevalence of misinformation about ED on social media platforms [1,2]. This is reassuring as AI chatbots continue to rise in popularity.…”
Section: Top Five Google Trend Queries Total (Googe Trends + Niddk He...mentioning
confidence: 76%
“…This is reassuring as AI chatbots continue to rise in popularity. A previous study suggested that healthcare professionals should take an active role in curating educational material on social media to reduce the amount of circulating misinformation [2]. In our study, ED content from AI chatbots were cited from reputable hospital and AUA‐affiliated organisations.…”
Section: Top Five Google Trend Queries Total (Googe Trends + Niddk He...mentioning
confidence: 87%
See 1 more Smart Citation
“…First, awareness of vasectomy has heightened as evidenced by Google searches for “vasectomy” that quadrupled following Dobbs , 10 and over 788 million TikTok views for #vasectomy. 11 Second, misconceptions regarding vasectomy may have been dispelled. Men inappropriately associate vasectomy with castration, testosterone deficiency, and sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients also provided testimonials of their experience on social media which were accurate and had little risk of misinformation. 11 Third, Dobbs has potentially shifted perceptions that contraception is a woman’s responsibility. Consumer reports show that 80% of US males feel responsible for pregnancy prevention; interviews of men in the post- Dobbs area have echoed these statements.…”
Section: Discussionmentioning
confidence: 99%